The Experience with a Surgical Camp in a Rural Hospital in Northern Uganda: A Descriptive Study - Wismayer, Richard (Issues and Developments in Medicine and Medical Research Vol. 2, 2022)
Introduction: In Sub-Saharan Africa, surgical conditions remain neglected in its health care systems. This results in a low surgical output from district hospitals with many patients referred to Referral Hospitals in the region. Therefore surgical camps in district hospitals are often necessary where volunteer surgical teams perform a wide range of mostly elective surgical procedures. These surgical camps are pre-planned activities carried out at no cost to the patients who belong to poor and hard to reach vulnerable communities. The objective of this surgical camp was to offer free specialised surgical service in a rural hospital and hence improve surgical access to a poor vulnerable community in Northern Uganda. Training basic surgical skills and the provision of continuous medical education to medical officers in the region was also part of the purpose of this surgical camp. Methods: A descriptive study using data collected from a one week surgical camp in the year 2011 was performed at St. Joseph’s Maracha Hospital. Data from operating log forms regarding date of procedure, patient gender, clinical diagnosis, operation performed and type of anaesthesia was obtained. Data was analysed for age, sex, type and rate of surgical procedure and type of anaesthesia. The participants’ involved specialist general surgeons, medical officers, clinical officers, theatre nurses and anaesthetists. Results: In total, 105 surgical procedures were performed during the 7-day-long camp. Mean age of the patients was 39.54 years. The male: female ratio was 1:0.38. Adult inguinal herniorrhaphy formed 68.6% of all surgical procedures. Conclusions: The bulk of surgical disease encountered during the camp were inguinal hernias. Surgical camps improve access to surgical care to vulnerable hard to reach populations and should become an integral part of health service delivery in rural Africa. Better knowledge and basic surgical skills resulting in better management of surgical cases by local medical officers is achieved with surgical camps.